Antibacterial Activities of the Ethanolic Extract of Crateva adansonii DC. (Capparidaceae) Harvested in Dassa-Zoumè in Central Bénin - mignanwande, Franck; JOHNSON, ROCH CHRISTIAN; HOUNKPATIN, Armelle Sabine Yélignan; BONI, GRATIEN; HOUNDETON, Geraldo; HOUETO, Enock M E; KPETEHOTO, H Wilfrid (My University, 2020)
Objective: The present was initiated to study the antibacterial properties of the Crateva adansonii DC extract on germs commonly identified in skin and digestive infections in Benin as well as the reversion of resistance to these aforementioned germs. Method: The bacteria’s sensitivity test to extracts was carried out by the microdilution method in liquid medium as well as the MIC and the reversion of bacterial resistance. For the determination of the MBC, this technique is used coupled with spreading on agar medium. Results: The results show an antibacterial activity of the extract with MICs between 0.625 - 5 mg/ml. The CMB of Enterococcus faecalis ATCC 29212 is 2.5 mg/ml while that of Methicillin-resistant Staphylococcus aureus and Staphylococcus epidermidis CIP 8039 is 5 mg/ml. The reversion of bacterial resistance has shown a synergy of action between our extract and conventional antibiotics.
Keywords: Antibacterial Activity; Crateva adansonii; Ethanolic Extract; Benin